2011
DOI: 10.1007/s10571-011-9720-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor Yellow A Protects PC12 Cells Against the Apoptosis Induced by Oxygen and Glucose Deprivation

Abstract: Hydroxysafflor yellow A (HSYA) was reported neuroprotective under several ischemic models in vivo. In this study, the direct effect of HSYA against oxygen-glucose deprivation (OGD) inducing acute neuronal injury and the underling mechanisms in vitro were investigated. Four-hour oxygen and glucose deprivation (OGD) followed by 20 h reperfusion (adding back oxygen and glucose, OGD-R) was used to induce in vitro ischemia reperfusion injury in differentiated rat pheochromocytoma PC12 cells. HSYA (1, 10, and 100 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 30 publications
(30 reference statements)
1
20
0
Order By: Relevance
“…It is widely reported that ROS directly acts on phospholipids to induce lipid peroxidation and produce MDA [20]. Therefore, MDA is a marker of lipid peroxidation and an end product of oxidative damage [21,22]. As expected, we found that OGD-R induced significant oxidative injury in HepG2 cells, which was manifested by a marked increase in MDA level.…”
Section: Discussionsupporting
confidence: 83%
“…It is widely reported that ROS directly acts on phospholipids to induce lipid peroxidation and produce MDA [20]. Therefore, MDA is a marker of lipid peroxidation and an end product of oxidative damage [21,22]. As expected, we found that OGD-R induced significant oxidative injury in HepG2 cells, which was manifested by a marked increase in MDA level.…”
Section: Discussionsupporting
confidence: 83%
“…Studies also reported that HSYA protects human umbilical vein endothelial cells against hypoxic injury by inhibiting cell apoptosis [44, 45]. Our previous in vitro [46] study demonstrated that HSYA can block oxygen and glucose deprivation followed by reperfusion (OGD-R) induced pc-12 apoptosis through suppression of intracellular oxidative stress and mitochondria-dependent caspase cascade. In the present in vivo study, we discovered that HSYA treatment significantly improved hindlimb motor disturbances after SCI.…”
Section: Discussionmentioning
confidence: 96%
“…25,26) It has been reported that HSYA exhibits antioxidative effects, alleviates oxidative stress. 19,27) In the rat brain, HSYA inhibits the opening of mitochondrial permeability transition pore by a free radical scavenging action. 28) Thus, it would be of great interest to identify the inhibitory effects of HSYA in protein glycation.…”
Section: Discussionmentioning
confidence: 99%